GOOGLE FORM SEBAGAI MEDIA EVALUASI PEMBELAJARAN SELAMA PANDEMI DI MIS AL-HANAFIYAH - Nur Aisyah; Khoirul Khoirul (Elementary School Teacher Education (PGSD), STKIP PGRI Sumenep, 2023)
This study focuses on the use of google forms as a medium for evaluating learning carried out at MIS Al-Hanafiyah during the pandemic. Using a qualitative approach to obtain a real picture of the condition of teachers and students while using the google form. The results showed that google form has advantages and disadvantages. The teacher makes a google form by considering the student's condition, learning objectives, and the type of questions to be given. Students who work on questions using google forms can immediately find out the value of the assignments given by the teacher.